2018
DOI: 10.21608/ejvs.2018.3855.1039
|View full text |Cite
|
Sign up to set email alerts
|

Iron Oxide Nanoparticles Versus Ferrous Sulfate In Treatment of Iron Deficiency Anemia In Rats

Abstract: F errous sulfate is the most commonly used drug for treatment of iron deficiency anemia, but it is badly absorbed and causes many unfavorable side effects. Nanotechnology is a way to decrease the side effects of drugs and to increase the drug bioavailability. So, this study is designed to investigate the effect of iron oxide nanoparticles in comparison to ferrous sulphate in the treatment of iron deficiency anemia in rats. Forty male albino rats were divided into two main groups: Control group (10 rats) and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…Additionally, the ascorbic acid absorbed by the M cells and increase the bioavailability of nano-iron to perform it is a vital role. These data are in agreement with those reported by [44][45][46] The results of kidney functions such as urea, uric acid, and creatinine referred to as the fortified biscuit plays a vital role in IDA treatment due to its high nutritional value. Moreover, there was not any non-significate effect appeared on the kidney from iron oxide nanoparticles.…”
Section: Hematology Serum Analysis and Growth Evaluationsupporting
confidence: 92%
“…Additionally, the ascorbic acid absorbed by the M cells and increase the bioavailability of nano-iron to perform it is a vital role. These data are in agreement with those reported by [44][45][46] The results of kidney functions such as urea, uric acid, and creatinine referred to as the fortified biscuit plays a vital role in IDA treatment due to its high nutritional value. Moreover, there was not any non-significate effect appeared on the kidney from iron oxide nanoparticles.…”
Section: Hematology Serum Analysis and Growth Evaluationsupporting
confidence: 92%
“…The current findings revealed a significant decrease in serum ferritin (iron store) and iron but an increase in TIBC in lead-acetate-induced anemic non-treated rats when compared to the negative control. The significant increase in TIBC could be due to the liver's increased production of transferrin in an attempt to maximize the utilization of the low available iron [57][58][59]. A similar result [60] showed that lead toxicity induced iron deficiency anemia by impairing heme biosynthesis.…”
Section: Discussionmentioning
confidence: 92%
“…It is necessary to develop new Fe supplements to increase Fe utilization and reduce its side effects ( 73 ). Nanotechnology is a means of decreasing the side effects while increasing its bioavailability ( 74 ).…”
Section: Biological Experimentsmentioning
confidence: 99%